2016
DOI: 10.1039/c6nr02730j
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the oxidase mimicking activity of nanoceria by fluoride capping: rivaling protein enzymes and ultrasensitive Fdetection

Abstract: Nanomaterial-based enzyme mimics (nanozymes) are currently a new forefront of chemical research. However, the application of nanozymes is limited by its low catalytic activity and low turnover numbers. Cerium dioxide nanoparticles (nanoceria) is among the few with oxidase activity. Herein, we report an interesting finding addressing its limitations. The oxidase activity of nanoceria is improved by over 100-fold by fluoride capping, rendering it more close to real oxidases (e.g., cytochrome P450). The turnover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
140
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 222 publications
(148 citation statements)
references
References 48 publications
(70 reference statements)
4
140
0
1
Order By: Relevance
“…When the surface active sites are consumed, the nanozyme became inactivated. A similar kinetic behavior was also observed for reacting CeO 2 with ABTS (CeO 2 being an oxidase‐mimic), and it was attributed to the adsorption of the oxidation product of ABTS inhibiting the adsorption of new substrates . A similar mechanism could also take place here such as by the products as an inhibitor.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…When the surface active sites are consumed, the nanozyme became inactivated. A similar kinetic behavior was also observed for reacting CeO 2 with ABTS (CeO 2 being an oxidase‐mimic), and it was attributed to the adsorption of the oxidation product of ABTS inhibiting the adsorption of new substrates . A similar mechanism could also take place here such as by the products as an inhibitor.…”
Section: Resultssupporting
confidence: 60%
“…For CeO 2 and Ce(IV), aside from the strong inhibition by phosphate, we only observed a weak inhibition effect of fluoride (Figure A, B), which is a reflection of its binding to cerium. Interestingly, F − boosted the oxidase‐like activity of CeO 2 , but it inhibited the oxidation ability of free Ce(IV) . For the phosphatase reaction, the accessibility of the surface Ce(IV) sites are apparently very important.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] In previous studies, ceria nanoparticles (nanoceria) and nanoceria-supported materials have been reported to have multi-enzyme mimetic activities like those of superoxide oxidase, [20,21] catalase [22,23] and oxidase. [24,25] That means nanoceria have enzymatic activities to catalyze the scavenging of reactive oxygen species (ROS). ROS are highly reactive and unstable compounds, with the ability to capture electrons from cellular macromolecules to damage proteins and DNA and to modify membrane fatty acids, thus impairing major cell functions.…”
Section: Introductionmentioning
confidence: 99%
“…We took advantage of the competitive adsorption of DNA and arsenate for its detection [24][25][26]. Similarly, hydrogen peroxide can displace DNA from cerium oxide [27], while fluoride can enhance its catalytic activity [28]. These specific interactions are useful for biosensor development.…”
Section: Introductionmentioning
confidence: 99%